2014
DOI: 10.1074/jbc.m114.577981
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Perfringolysin O D1 Domain in Orchestrating Structural Transitions Leading to Membrane-perforating Pores

Abstract: Background: Pore formation by perfringolysin O consists of well defined stages, but the mechanism is not fully understood. Results: We mapped regions in toxin that undergo stabilization and destabilization upon oligomerization. Conclusion: Properly folded D1 orchestrates structural transitions in other domains necessary for pore formation. Significance: Study of structural changes in cytolysin domains upon binding to membrane is crucial for understanding pore formation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The method was performed as described previously [37], with minor modifications. Initially, the list of peptides was established by diluting each analyzed protein to 5–10 μM in a non-deuterated buffer (20 mM Hepes pH 6, 100mM KCl).…”
Section: Methodsmentioning
confidence: 99%
“…The method was performed as described previously [37], with minor modifications. Initially, the list of peptides was established by diluting each analyzed protein to 5–10 μM in a non-deuterated buffer (20 mM Hepes pH 6, 100mM KCl).…”
Section: Methodsmentioning
confidence: 99%
“…Two control experiments were performed to account for in-and out-exchange artifacts, as described previously (Kacprzyk-Stokowiec et al, 2014). In brief, to assess minimum exchange (in-exchange control), D 2 O reaction buffer was added to stop buffer that had been cooled on ice prior to addition of protein stock, and this mixture was immediately subjected to pepsin digestion and LC-MS analysis as described above.…”
Section: Hydrogen-deuterium Exchangementioning
confidence: 99%
“…D3 does not directly contact D4, but forms an interface with both D1 and D2 that connects D3 with D4 ( Figure 1 , Figure 5 b) [ 30 , 31 , 43 ]. The stability of D1 increases upon membrane binding, which may be important for disengagement of the D2,3 interface [ 71 ]. When D1 is destabilized by the substitution of a tryptophan residue (Trp-165 in PFO), the interface between D2,3 fails to disengage [ 63 , 71 ].…”
Section: Molecular Mechanism Of Pore Formationmentioning
confidence: 99%
“…The stability of D1 increases upon membrane binding, which may be important for disengagement of the D2,3 interface [ 71 ]. When D1 is destabilized by the substitution of a tryptophan residue (Trp-165 in PFO), the interface between D2,3 fails to disengage [ 63 , 71 ]. Additionally, Wade et al [ 72 ] recently showed that the rotation of β5 away from the core β-sheet in D3 allows the formation of a strong intermolecular electrostatic interaction, which drives the transition from the prepore to the pore by providing the free energy necessary to disrupt the interface between D3 and D1,2.…”
Section: Molecular Mechanism Of Pore Formationmentioning
confidence: 99%
See 1 more Smart Citation